PENGAWASAN KESELAMATAN PENERBANGAN BANDAR UDARA SAM RATULANGI OLEH KANTOR OTORITAS BANDAR UDARA WILAYAH VIII MANADO - PAPIA, JERRI YEREMIA; TULUSAN, FEMMY; DENGO, SALMIN (JURNAL ADMINISTRASI PUBLIK, 2017)
Abstract: the quality of human resources holds an important role, because people involved in a flight not just pilots, butalso of other officers, including those responsible for the handling and inspection of aircraft research objectives this is tofind out the flight safety supervision of Sam Ratulangi Airport by the Airport Authority Region VIII Manado.This research uses qualitative approach method. This research is focused on the efforts and actions undertaken to achieveaviation safety at the airport, both preventive (preventive supervision) as well as the repressive nature of the (repressivesupervision). Informants in this study is taken from the elements directly related to aviation activities at the airport: AirportAuthority, airlines, and passengers on the plane.The results showed that the repressive surveillance carried out by doing the monitoring, inspection, and direct assessmentof all aspects/fields related to aviation safety at the airport be scope the duties and functions of the Office of the AirportAuthority Region VIII Manado as flight safety, aircraft, flight navigation services activities, the fulfilment of standardscertification flight navigation areas, emergency response documents aviation security, the implementation of permitapproval routes to and from airports, satisfy the standards activities of the Airport related services, service air freightactivities, implementation of the Flight Approval (FA), the implementation of permit route, implementation of air transportfares, and against environmental management of airports. Repressive supervision over all aspects related to the safety ofthe flight not been fullest. The constraints of the repressive surveillance also is the limited human resources Office of theAirport Authority Region VIII Manado either in quantity or quality, of the means of implementing surveillanceinfrastructure is not yet fully available/are met; and coordination with related parties has not been fully realized properly.The implications of the results of such research is the need to increase the number of employees of the Office of the AirportAuthority Region VIII Manado, improve the quality of human resources officers, and improve coordination with the bestthere is at the airport, The study also shows that although the oversight of aviation safety Sam Ratulangi Airport by theAirport Authority Region VIII Manado is still not a maximum, but with preventive and repressive supervision performedduring this have been able to improve flight safety guarantees. Based on the research of aviation safety assurance at SamRatulangi airport, makin good as realized by decreasing the number of accidents of air transportation; decrease in the levelof air transport security disruptions; increasing the performance of the service of air transportation facilities andinfrastructure; and increasing air transportation service. This means that if the role of the Office of the Airport Authorityin the oversight of aviation safety can be enhanced or maximized, then certain flight safety will come true better yet.Keywords: surveillance, aviation safety, the Airport Authority